A study on the viable regulatory model governing elderly care in Malaysia / Norfadzilah Abd Wahab, Noor Asyikin Md Rodhi and Nur Amaliana Mohd Ramli - Abd Wahab, Norfadzilah; Md Rodhi, Noor Asyikin; Mohd Ramli, Nur Amaliana (2010)
this paper asks what the best model of elderly care to be adopted by our country is by comparing the models of law in Singapore and the welfare system in the US. Basically, Chapter 1 of this paper will be discussing on the filial piety on the part of the children towards their parents. The next chapter will be a literature reviews on the problem or challenges to the senior citizens from many aspects of life such as social, economic and health care. The examples of elderly protection by laws and welfare system will be explained under Chapter 3 by discussing on the models of filial responsibility law regulated by Singapore and the welfare system exercised by US government. Chapter 4 of this paper will be focusing on the policy and the laws on elderly care in Malaysia i.e. The National Social Policy 1990, the Health Care programme, and the EPF. Although Malaysia is not in a position to adopt both models which are having different approach, it might be possible to adopt some of the mechanism laid down under the filial responsibility law or the welfare system into our administration of law with regards of elderly care.